Potential Impact of Mediterranean Aquaculture on the Wild Predatory Bluefish. Issue 1 (1st January 2016) - Miralles, L.; Mrugala, A.; Sanchez-Jerez, P.; Juanes, F.; Garcia-Vazquez, E.
Abstract: Aquaculture impacts on wild populations of fish have been considered principally due to farm escapes. The Bluefish Pomatomus saltatrix, which exhibits two distinct genetic units in the Mediterranean Sea, is a voracious predator and is attracted to aquaculture cages to prey on farmed fish, particularly Gilthead Seabream Sparus aurata and European Sea Bass Dicentrarchus labrax . We compared the genetic diversity of adult Bluefish caught inside one aquaculture farm located in Spanish waters of the western Mediterranean Sea with reference individuals of East and West Mediterranean stocks from the open sea. Bluefish were genetically assigned to their putative origin using seven microsatellite loci and mitochondrial cytochrome oxidase subunit I as molecular markers. As expected, most of the individuals caught from inside the fish farm cages were assigned to the local genetic population. However, between 7.14% and 11.9% of individuals were assigned to the distant and different genetic unit inhabiting Turkish waters, the East Mediterranean stock. The genetic membership of those individuals revealed some degree of interbreeding between the East and West Mediterranean Bluefish stocks. All results suggest that aquaculture acts as an attractor for Bluefish and could affect genetic diversity as well as phylogeography of this fish and maybe other similar species that aggregate around marine fish farms. Received July 11, 2015; accepted November 23, 2015